The degree at which the first three basic grades pupils practice the ethical values from the point of view of their teachers in the Southern Ghors District - Al-Khleifat, Anwar Eisa Salmeh; Al-khleifat, Ali Salmeh Daowd (Journal of Educational and Psychological Sciences, 2020)
This study aimed at identifying the degree at which the first three basic grades pupils practice the ethical values from the point of view of their teachers in the Southern Ghor District، as well as، the relationship of that with some variables. The researchers developed the study tool that consisted of، ( 27 ) items divided into three domains; the validity and reliability of the study tool were verified. The study sample consisted of (50) female teachers from those who teach the first three basic grades. The study results showed that، the degree at which the first three basic grades pupils practice the ethical values from the point of view of their teachers in the Southern Ghor، District، was high. The domain relating to (the relationship between the pupil and the teaching staff) was in the first place، followed by (the relationship between the pupil and his teacher)، and finally (the relationship between the pupil and his peers). The results showed that there are no statistically significant differences at ( α≤ 0.05 )، regarding the degree at which the first three basic grades pupils practice the ethical values from the point of view of their teachers in the Southern Ghor District attributed to the variables of the years of experience as well as educational qualification. In the light of the results، the study recommended that، the students should practice the ethical values in a high degree with their peers by educating the pupils regarding the brotherhood in our Islamic religion as well as practicing these behaviors in front of the students to reinforce them. The study also recommended about conducting a study that reveals the degree at which the secondary stage students practice the ethical values from the point of view of their teachers in the Southern Ghor District.
Keywords: practice degree; the first three basic grades; ethical values